Fa‘atama: Indigenous Tomboys of Sāmoa - Mandy Treagus; Dion Enari (eTropic: electronic journal of studies in the tropics)
This paper acknowledges that queerness has always existed in the tropics, especially in Sāmoa. In traditional Sāmoan life, there has always been more than two genders. While much attention has been given to fa‘afafine, we seek to raise the visibility of another queer group, fa’atama (formally fa‘atane) or tomboys—Sāmoans assigned female at birth (AFAB), who either identify as masculine, are attracted to females, or both. Not only is this group marginalised on the world stage, but also within Sāmoan and Pacific culture, which has suppressed their lives and identities. In the context of a very specific historical and cultural milieu, we examine three recent representations—in poetry, fiction, and film—of queer AFAB Sāmoans in order to privilege their stories.